Interferometry for full temporal reconstruction of laser-plasma accelerator-based seeded free electron lasers. (27th January 2020) - Labat, M; Bielawski, S; Loulergue, A; Corde, S; Couprie, M-E; Roussel, E
Abstract: The spectacular development of Laser-Plasma Accelerators (LPA) appears very promising for a free electron laser application. The handling of the inherent properties of those LPA beams already allowed controlled production of LPA–based spontaneous undulator radiation. Stepping further, we here unveil that the forthcoming LPA–based seeded FELs will present distinctive spatio-spectral distributions. Relying on numerical simulations and simple analytical models, we show how those interferometric patterns can be exploited to retrieve, in single-shot, the spectro-temporal content and source point properties of the FEL pulses.